A project feasibility study for cad oil (Rolling Oil) - Tagamolila, John Mark D. (College of Engineering, 1995)
The project name is CAD OIL (rolling oil). This is a lubricant used in the manufacture of cold rolled steel sheets and plates. The rolling oil prepares the steal prior to milling to reduce the shear force. This shear force produces undesirable results in the finished product such as mechanical strain. In the market study, it was established that there is a demand for the product. The company simply meets the specification of the rolling oil that is used by National Steel Corporation (NSC). The selling prices of the product are set at P30 per liter of P 6,000 per barrel (1 barrel = 200 liters) for a production volume of 6685 barrels. This selling prices if half of the competitor's selling price. NSC is the only manufacturer of cold rolled steel sheets and plates in the Philippines. To ensure of a market, the policy of NSC concerning supplier of raw materials is meet by the company. The manufacturing process used to price the product is an available technology. The process undergoes fat splitting, separation and mixing of the raw materials to come up with the finished product. All of the raw materials and supplies, equipments, labor and utilities will be sourced locally except for some that is unavailable and there is no enough supply. Those exceptions require importation of animal fat and centrifuge. The plant is located within NSC Compound, Iligan City, Lanao del Norte. The plant size and layout were designed according to the manufacturing process and the project demand for the product. Building and facilities are designed according to the manufacturing process and other necessary operations. A waste water treatment facility will be installed to comply with the regulations of Department of Environment and Natural Resources regarding environmental standards. The production cost of the product is P 24,008,099.60. The unit product costs excluding and including operating expense are P 3,591.34 and P 3,893.90. The project can generate enough revenue with its selling price of P 6,000. The project will be financed by the NSC, the firm and a commercial bank. The firm and NSC will enter into a partnership wherein the capital investment share of both parties is equal (P 1M/party). The remaining amount will be sourced from a loan in a commercial bank. The project used the manufacturing process of the rolling oil of the prior project feasibility study. However, some operations are omitted due to a change of raw materials. The various tests of operational efficiency show that the project has a very good performance and efficiency. The test of capital investment evaluated that the project is profitable. The project has a positive net present value of 25% rate of return. It shows that the project is acceptable and good as investment. The internal rate of return of the project is 76%. It means that the project will generate profits in short time. The project is viable and profitable. The project will generate labor within the area for 9 persons. The project will lessen dollar spending of the government with the elimination of importation of rolling oil. The project is environment-friendly since it does generate any toxic waste. The project is found to be feasible in all aspects: market, technical, financial and social.